Determination of the elastic moduli and residual stresses of freestanding Au-TiW bilayer thin films by nanoindentation. (15th September 2016) - Ghidelli, Matteo; Sebastiani, Marco; Collet, Christian; Guillemet, Raphael
Abstract: In this paper, we present a detailed mechanical characterization of freestanding bilayer (Au-TiW) micro-cantilevers and double clamped beams, for applications as Radio Frequency (RF)-switches Micro-Electromechanical Systems (MEMS). The testing structures have been characterized by an optical profilometer and Scanning Electron Microscopy (SEM) equipped with Energy Dispersive X-ray Spectroscopy (EDS), in order to acquire information about their geometries, composition, and the gap between the substrate underneath. Then, the micro-beams are deflected by using a specifically designed nanoindentation procedure based dynamic stiffness measurement during bending in order to extract the elastic modulus and the residual stresses of both layers. Firstly, the classic beam theory has been implemented for bilayer cantilevers enabling the extraction of elastic moduli. Then, residual stresses are estimated by deflecting double clamped beams, while implementing new analytical models for a bilayer system. The obtained elastic moduli are consistent with the average ones obtained for a single layer micro-cantilever and with nanoindentation results for TiW and Au homogeneous films. The residual stresses are in agreement with the values obtained from the double slot Focused Ion Beam (FIB) and Digital Image Correlation (DIC) procedure, providing an alternative and portable way for the assessment of residual stresses on composite double clamped micro-beams. Graphical abstract: Highlights: A new method for the assessment of elastic moduli and residual stresses in bi-layer suspended micro-beams is presented The method is based on micro-bending experiments performed by nanoindentation testing An analytical procedure is adopted to extract the elastic modulus and residual stress of each layer Nanoindentation method is validated by Focused Ion Beam - Digital Image Correlation (FIB-DIC) double-slot technique The developed procedures can be useful for design of Microelectromechanical devices with improved performance